2014
DOI: 10.1111/ans.12886
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of osteotomy versus non‐osteotomy approach for congenital scoliosis: a retrospective study of three surgical techniques

Abstract: BackgroundCurrently, there are many reports about congenital scoliosis (CS) treatment, but there are still controversies existing with respect to selecting its surgical methods.MethodsRetrospective analyses were conducted on 31 CS patients. The surgical treatments included the following: posterior instrumentation (10 patients; group 1), pedicle subtraction osteotomy (11 patients; group 2) and vertebral column resection (10 patients; group 3).ResultsAll patients had remarkable improvements in morphology, image … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
2
0
3
Order By: Relevance
“…It is noteworthy to note the liberal use of spinal column shortening osteotomies and avoiding distraction manoeuvres in NNI group especially for rigid and severe deformities. Despite the use of osteotomies in most studies in the NI group, the authors managed only a modest deformity correction when compared with the reported correction rate with osteotomies in the existing literature [40][41][42][43]. This controlled deformity correction may be attributable to the fear of neurological complications associated with overzealous deformity correction manoeuvres.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It is noteworthy to note the liberal use of spinal column shortening osteotomies and avoiding distraction manoeuvres in NNI group especially for rigid and severe deformities. Despite the use of osteotomies in most studies in the NI group, the authors managed only a modest deformity correction when compared with the reported correction rate with osteotomies in the existing literature [40][41][42][43]. This controlled deformity correction may be attributable to the fear of neurological complications associated with overzealous deformity correction manoeuvres.…”
Section: Discussionmentioning
confidence: 93%
“…On overall analysis, no statistically significant difference was observed between the two study groups (MD = 1537.64; 95%CI-1107.71, 1967.56 vs MD = 1640.57; 95% CI-1302. 40,1978.74) (Fig. 6).…”
Section: Operative Parametersmentioning
confidence: 98%
“…Анализируя работы, в которых рассматривается оперативное лечение пациентов с врожденной деформацией позвоночника, нельзя не заметить отсутствие единого мнения относительно оптимального хирургического подхода к телу аномального позвонка при оперативном лечении детей с данной патологией. Некоторые авторы доказывают возможность оптимальной коррекции врожденной деформации позвоночника только из дорсального доступа [7][8][9][10], другие -утверждают, что наилучшие результаты дает вмешательство из комбинированного доступа (переднебокового и дорсального) [4,[11][12][13][14]. Одновременно с этим остается открытым вопрос протяженности  Ортопедия, травматология и восстановительная хирургия детского возраста.…”
unclassified
“…2019 металлофиксации при различных вариантах хирургического подхода в лечении детей с врожденными искривлениями позвоночника. Одни авторы считают, что коррекцию врожденной деформации необходимо проводить, фиксируя минимальное количество позвоночно-двигательных сегментов и стабилизируя только соседние позвонки отно сительно аномального [5,15,16], другиеутверж дают, что исправление врожденной деформации необходимо осуществлять многоопорной металлоконструкцией с фиксацией позвонков, расположенных на протяжении нескольких позвоночно-двигательных сегментов выше и ниже порочного позвонка [11]. Однако ни в одном исследовании не был проведен сравнительный анализ количества стабилизированных позвоночно-двигательных сегментов с помощью спинальной системы при различных хирургических доступах коррекции врожденной деформации у пациентов детского возраста.…”
unclassified
“…Особенно актуальной задачей является коррекция врожденной деформации позвоночника в области грудопоясничного перехода. Ряд специалистов предлагают осуществлять хирургическое вмешательство из комбинированного подхода (переднебокового и дорсального) [7][8][9]. Другие авторы рекомендуют для коррекции врожденного кифосколиоза грудопоясничного отдела позвоночника использовать только задний доступ [10][11][12].…”
unclassified